2021
DOI: 10.1007/s00405-021-07086-9
|View full text |Cite
|
Sign up to set email alerts
|

Does the wearing of masks change voice and speech parameters?

Abstract: Purpose The authors aim to review available reports on the potential effects of masks on voice and speech parameters. Methods A literature search was conducted using MEDLINE and Google Scholar databases through July 2021. Several targeted populations, mask scenarios and methodologies were approached. The assessed voice parameters were divided into self-reported, acoustic and aerodynamic. Results It was observed that the wearing of a face mask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Perception of speech was affected by mask in particular for the perception of bilabial syllables regardless of modality, suggesting that wearing a mask impairs the production of syllables involving the lips, consistent with reports that face mask alters speech articulatory movements (Gama et al, 2021). However, we did not find a general impact of masks on intelligibility, contrary to Cohn et al (2021) who reported altered perception for casual and positive speech, possibly due to controlling for intensity across masked and unmasked condition (Gama et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…Perception of speech was affected by mask in particular for the perception of bilabial syllables regardless of modality, suggesting that wearing a mask impairs the production of syllables involving the lips, consistent with reports that face mask alters speech articulatory movements (Gama et al, 2021). However, we did not find a general impact of masks on intelligibility, contrary to Cohn et al (2021) who reported altered perception for casual and positive speech, possibly due to controlling for intensity across masked and unmasked condition (Gama et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…Voice recognition has also been applied for the prediction and evaluation of health conditions, such as mental health and emotional condition ( Pisanski et al, 2016 ; Holmqvist-Jämsén et al, 2017 ; Dibeklioglu et al, 2018 ; Pisanski and Sorokowski, 2021 ; Kappen et al, 2022 ). Recently, it has been applied to respiratory diseases such as COVID-19 to detect the health conditions of the patients and monitor the emotional states of the staff ( Castillo-Allendes et al, 2021 ; König et al, 2021 ; Gama et al, 2022 ). However, no vocal biomarkers have been approved by the US Food and Drug Administration or the European Medicines Agency so far.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the long-term effects of continued mask wearing have been investigated in only a few studies to date [ 35 , 36 , 37 , 38 ]. These suggest that the continued wearing of face masks may also have negative consequences, and these must be carefully balanced against the advantage of reduced infection rates.…”
Section: Discussionmentioning
confidence: 99%